2013
DOI: 10.1038/srep02226
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic catalysis using amphiphilic polyphenols-chelated noble metals as highly active and selective catalysts

Abstract: In the field of catalysis, it is highly desired to develop novel catalysts that combine the advantages of both homogeneous and heterogeneous catalysts. Here we disclose that the use of plant pholyphenol as amphiphilic large molecule ligand/stabilizer allows for the preparation of noble metal complex and noble metal nanoparticle catalysts. These catalysts are found to be highly selective and active in aqueous-organic biphasic catalysis of cinnamaldehyde and quinoline, and can be reused at least 3 times without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
(20 reference statements)
2
15
0
Order By: Relevance
“…Particularly in the catalytic reaction process, bimetallic NPs often exhibit higher catalytic activity and selectivity than their monometallic counterparts 9 . Though, the recovery and reusability of the homogeneous catalysts is extremely difficult and often requires tedious process 1,4,10 . Apparently, there is an acute need for developing a new type of catalyst that process high efficiency and reusability.…”
mentioning
confidence: 99%
“…Particularly in the catalytic reaction process, bimetallic NPs often exhibit higher catalytic activity and selectivity than their monometallic counterparts 9 . Though, the recovery and reusability of the homogeneous catalysts is extremely difficult and often requires tedious process 1,4,10 . Apparently, there is an acute need for developing a new type of catalyst that process high efficiency and reusability.…”
mentioning
confidence: 99%
“…A few examples of unimolecular macrostructures that achieve a favorable environment for efficient catalysis in water are available in the open literature, yet with various architectures http://dx.doi.org/10.1016/j.jcat.2015.01.009 and levels of complexity. Using natural polyphenols as amphiphilic ligands, Mao et al [14] could prepare noble metal complex and noble metal nanoparticle catalysts for the biphasic hydrogenation of cinnamaldehyde and quinoline. The authors observed some decrease of conversion upon recycling, whose extent depended on the content of polyphenols: from 61% to 97% of the original activity was retained after five runs.…”
Section: Introductionmentioning
confidence: 99%
“…The peak at ÎŽ 8.544, noted as H b , not connected with any C atoms ( S. Fig. 6 ), but in the range of active H, is assigned to OH group 13 16 17 . The peak at ÎŽ 3.892, noted as H c , connected with C atoms at ÎŽ 71.80, is assigned to CH group ( S. Fig.…”
Section: Resultsmentioning
confidence: 99%